Review and Prospect of Research on Urban Walking Safety and Environmental Influencing Factors Thereof - Lin LI; Yu YE; Yong CHEN (Fengjing Yuanlin)
ObjectiveWalking space is an important part of urban public space, and its spatial quality is a basis for the construction of walkable cities, which directly affects residents’ travel willingness and walking experience.MethodsThis research takes relevant literature on walking safety screened from Web of Science and CNKI databases spanning the period from 1975 to 2022 as research object, and analyzes the distribution characteristics of literature related to the current research on walking safety and environmental influencing factors thereof, as well as such contents as research context and research hotspots.ResultsFirstly, from the perspective of literature distribution, a large number of works of scholars in such fields as traffic engineering, public health and sociology have been cited in literature on walking safety, reflecting that pedestrians’ activity safety, traffic safety and security needs are important directions to promote the research on walking safety. At present, the research on walking safety in developed countries is more active and fruitful. The advanced urbanization process and prominent social contradictions make developed countries and regions more capable of investing energy and funds in walking safety research, exploring the safety issues faced by vulnerable road users, and deepening the degree of research refinement. Secondly, from the perspective of research evolution, the research has the following findings. 1) The analysis results of highly cited literature concerns show that walking safety and walkers’ safety perception dominate the development direction of relevant research. 2) Based on WoS database, the analysis of theme words shows that taking accident analysis as the core, taking pedestrian characteristics as the perspective and taking new technology as the guidance are the three major topics in the field of walking safety research. New data and technologies support the analysis of core environmental factors influencing walking safety. 3) Based on CNKI database, the analysis of keywords shows that domestic research focuses on the spatial quality of walking environment and the special needs of vulnerable walkers, and it is urgent to establish a walking safety environment evaluation system in China. In addition, the keyword analysis also shows that the impact of built environment on pedestrian safety accidents and pedestrian safety perception has become a focus of attention. Thirdly, from the perspective of research hotspot, it can be seen form the three dimensions of activity safety, traffic safety and security that, different levels of environmental elements such as neighborhoods, streets and intersections, have important influence on walking safety. In recent years, the extensive application of quantitative analysis and data calculation methods has brought new ideas and technologies to the research. Especially in the field of data mining regarding urban form and walkers’ psychological perception, new technologies are helpful for in-depth analysis of the influence of built environment factors on walking safety. Finally, the research trend of walking safety is reflected in three aspects: Research object, content and method. Research object has expanded from collision accident to walkers’ psychological perception, and researchers increasingly pay attention to the influence of the safety quality of walking environment on pedestrian psychology. As the urban built environment is facing more and more complex conditions, the research focus extends from the analysis of individual collision accidents to the comprehensive urban environment construction. Research methods have also been developed from single-specialty technical analysis to multi-dimensional integrated research, which promotes the comprehensive application of research methods from such fields as environmental psychology, traffic safety and road engineering in the research on walking safety.ConclusionThis research reveals the development direction, main context and research hotspots on walking safety and environmental influencing factors thereof, highlights the significant influence of multi-level built environment factors on walking safety and walkers' safety perception, and provides theoretical support for empirical researches on walking safety environment. In future research, it is necessary to conduct collaborative thinking on walking safety and pedestrian safety perception, promote the applicability of relevant research technologies, and pay attention to the influence of the development of emerging transportation technologies on the safety quality of walking environment.